A Review Of Mircea Eliade's Perspective On The Sacred Symbols Of The Ka'bah And The Cross - Vera Sari; Lalu Pradipta Jaya Bahari (ASTEEC, 2024)
Symbols of sacredness such as the Kaaba and the cross play a central role in Islamic and Christian traditions, representing spiritual, theological, and sociocultural aspects. This research examines the sacred dimensions of these two symbols using the perspective of Mircea Eliade, known for his phenomenological approach to understanding religion and symbolism. The main issues raised are how the Kaaba and the cross can become sacred centers of spirituality, and how their symbolic meanings are understood in a cross-religious and cultural context. This research explores the meaning and function of the Kaaba and cross symbols, using a qualitative method based on comparative studies. Data collection techniques were conducted through a literature review that included books, academic articles, and other relevant documents. Data were analyzed through the classification, reduction, and interpretation stages, focusing on the relationship of these symbols to religious experience and socio-cultural context. The results show that the Kaaba, as the center of Muslim worship, is a symbol of spiritual unity associated with monotheism, while the cross in the Christian tradition symbolizes victory over sin and death, and is central to the sacrificial theology of Jesus Christ. Both symbols function as manifestations of hierophany, as per Eliade's theory, which creates a sacred space in the midst of worldly life. The research also reveals the role of the Kaaba and the cross as a means of forming the collective identity of their respective communities, whose relevance is maintained despite the challenges of modernity.